(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This study investigates how technical management and product management influence the adoption of smartwatches in Shenzhen, China, emphasizing the mediating role of management innovation. Situated in one of the world’s most dynamic technology hubs, the research explores the strategic interplay between engineering, product development, and organizational innovation within the region’s competitive smartwatch industry. Drawing on an interpretive qualitative approach, data were collected through in-depth interviews with 26 senior managers, product strategists, and technical experts across leading smartwatch firms. Thematic analysis revealed three overarching themes: (1) the strategic alignment of technological capabilities with market demands, (2) innovation as a systemic organizational capability, and (3) management innovation as a dynamic integrator linking technical potential to market impact. Findings show that successful smartwatch adoption depends not only on technical excellence or market insight but on the ability of firms to bridge these domains through agile management structures, cross-functional collaboration, and open innovation practices. Management innovation emerges as a pivotal enabler of organizational ambidexterity, allowing firms to balance exploration and exploitation while maintaining responsiveness to consumer trends. The study extends theories of innovation management by demonstrating how internal cultural shifts, structural redesign, and leadership practices support product adoption in fast-paced, resource-constrained environments. Implications for future research, policy, and managerial practice are discussed, offering insights into how emerging-market firms can foster sustainable innovation through adaptive and integrative management approaches.